Chemical analysis and sensory evaluation of honey produced by honeybee colonies fed with different sugar pastes. Issue 11 (24th September 2020) - Moumeh, Bouchra; Dolores Garrido, María; Diaz, Pedro; Peñaranda, Irene; Linares, María Belén
Abstract: Supplemental feeding of honeybee ( Apis mellifera L .) colonies is essential for colony buildup. Honey samples obtained from feeding honey bee colonies with different commercial sugars, including sugar paste, sugar paste + vitamins +amino acids, and sugar paste + vitamins +protein as pollen substitute, were studied to determine the effects of feeding bees on the physicochemical and sensory characteristics of honey, compared with the honey produced by a control group (no supplemental feeding). Analyzed honey samples from the different groups were in accordance with the criteria described in Council directive 2001/110/CE, 2002. Elsewhere, significant differences ( p  > .05) were detected in color, free acidity, diastase activity, hydroxymethylfurfural, sugar profile, and conductivity between all honey. In terms of mineral content, the honey from hives faded with sugar paste + vitamins +protein and control group had higher values for Na, Mg, P, K, Ca, Mn, Fe, Cu, and Zn. Related to sensory analyses, no differences in flavor and basic taste were found in all analyzed honey ( p  > .05) independently the type of feeding. For the visual attributes, only differences were found for the color. Supplementary feeding with different sugar pastes and proteins does not affect the physicochemical characteristics of honey. For the sensory analyses, control sample presented significant differences only for color and chemical odor attributes compared with honey from bees receiving supplementation. Abstract : This paper is based on the effect of feeding supplementation of honeybee and the effect on honey quality.